Reinvigorating Civil–Military Relationships in Building National Resilience. Issue 4 (4th July 2017) - Zekulić, Vlasta; Godwin, Christopher; Cole, Jennifer
Abstract : Russia's application of a sophisticated hybrid strategy and the rise of Daesh (also known as the Islamic State of Iraq and Syria, ISIS) have been drivers for change in the complex security environment of the twenty-first century. While the significance of these threats does not preclude the conventional aspect of national defence planning, it does complicate societal preparedness. Vlasta Zekulić, Christopher Godwin and Jennifer Cole examine the relevance of NATO resilience policies and propose a synchronised approach to crisis decision-making, civil preparedness planning and national and collective defence to ensure they are balanced, mutually supportive and incur manageable cost.